PENERAPAN METODE EKSPERIMEN UNTUK MENINGKATKAN SIKAP ILMIAH SISWA DALAM PEMBELAJARAN IPA DI KELAS V SDN KELAPA DUA 06 PAGI JAKARTA - Soraya, Rindra; Syofyan, Harlinda (Eduscience : Jurnal Ilmu Pendidikan, 2017)
AbstractThis research is aimed: (1) to know the process of learning science in the fifth grade by using experimental method; (2) to know students' scientific attitude of learning science in the fifth grade by using experimental method; (3) to know the application of experimental method can improve student's scientific attitude of learning science in the fifth grade. This type of research is classroom action research (PTK). The design of this research using Kemmis and Taggart model. The subject of this research is the fifth grade students as many as 25 students. This study was conducted in two cycles, each cycle twice a meeting. Data collection techniques include observation, diaries, interviews, and documentation. Data analysis in this research use descriptive statistic. Indicators of successful research if it has reached ≥80%. The results of this study on the first cycle of teacher activity using experimental methods of 72. 73% and students' scientific attitude of 68. 78%, Increased in the second cycle of teacher activity using experimental method of 95. 46% and students' scientific attitude of 82. 13%. This research concludes that the application of experimental method can improve the students' scientific attitude in learning natural science of elementary school fifth grade Kelapa Dua 06 Jakarta Keywords: experimental method, scientific attitude, science learning AbstrakPenelitian ini bertujuan untuk: (1) mengetahui proses pembelajaran IPA di kelas V dengan menggunakan metode eksperimen; (2) mengetahui sikap ilmiah siswa dalam pembelajaran IPA di kelas V menggunakan metode eksperimen; (3) mengetahui penerapan metode eksperimen dapat meningkatkan sikap ilmiah siswa dalam pembelajaran IPA di kelas V. Jenis penelitian ini adalah penelitian tindakan kelas (PTK). Desain penelitian ini menggunakan model Kemmis dan Taggart. Subjek penelitian ini adalah siswa kelas V sebanyak 25 siswa. Penelitian ini dilakukan dalam dua siklus, setiap siklus dua pertemuan. Teknik pengumpulan data meliputi observasi, catatan harian, wawanacara, dan dokumentasi. Analisis data pada penelitian ini menggunakan statistika deskriptif. Indikator keberhasilan penelitian apabila telah mencapai ≥80%. Hasil penelitian ini pada siklus I aktivitas guru menggunakan metode eksperimen sebesar 72, 73% dan sikap ilmiah siswa sebesar 68, 78%, meningkat pada siklus II aktivitas guru menggunakan metode eksperimen sebesar 95, 46% dan sikap ilmiah siswa sebesar 82, 13%. Penelitian ini menyimpulkan bahwa penerapan metode eksperimen dapat meningkatkan sikap ilmiah siswa dalam pembelajaran IPA kelas V SDN Kelapa Dua 06 Pagi Jakarta Kata kunci: metode eksperimen, sikap ilmiah, pembelajaran IPA